Super tricky limit problem

Calculus Level 3

The largest value of the nonnegative integer a a for which lim x 1 { a x + sin ( x 1 ) + a x + sin ( x 1 ) 1 } 1 x 1 x = 1 4 \displaystyle\lim_{x\to1}\left\{\dfrac{-ax + \sin(x-1) + a}{x + \sin(x-1) - 1}\right\}^\frac{1-x}{1-\sqrt{x}} = \dfrac{1}{4}
is?

Problem first appeared in JEE Advanced 2014.

1 0 2 4

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Naren Bhandari
May 26, 2018

We have sin ( x 1 ) = ( x 1 ) ( x 1 ) 3 3 ! + ( x 1 ) 5 5 ! + \sin (x-1) =(x-1) -\frac{(x-1)^3}{3!} + \frac{(x-1)^5}{5!} +\cdots lim x 1 { a x + sin ( x 1 ) + a x + sin ( x 1 ) 1 } 1 x 1 x = 1 4 lim x 1 { a ( x 1 ) + sin ( x 1 ) x 1 + sin ( x 1 ) } 1 + x = 1 4 lim x 1 { a ( x 1 ) + ( x 1 ( x 1 ) 3 3 ! + ( x 1 ) 7 7 ! + ) x 1 + ( x 1 ( x 1 ) 3 3 ! + ( x 1 ) 7 7 ! + ) } 1 + x = 1 4 lim x 1 { a + ( 1 ( x 1 ) 3 3 ! ( x 1 ) + ( x 1 ) 7 7 ! ( x 1 ) + ) 1 + ( 1 ( x 1 ) 3 3 ! ( x 1 ) + ( x 1 ) 7 7 ! ( x 1 ) + ) } 1 + x = 1 4 lim x 1 { a + ( 1 ( x 1 ) 2 3 ! + ( x 1 ) 6 7 ! + ) 1 + ( 1 ( x 1 ) 2 3 ! + ( x 1 ) 6 7 ! + ) } 1 + x = 1 4 lim x 1 { a + 1 1 + 1 } 1 + 1 = 1 4 ( a + 1 ) 2 4 = 1 4 a = 0 , 2 \displaystyle\lim_{x\to1}\left\{\dfrac{-ax + \sin(x-1) + a}{x + \sin(x-1) - 1}\right\}^\frac{1-x}{1-\sqrt{x}} = \dfrac{1}{4}\\ \displaystyle\lim_{x\to1}\left\{\dfrac{-a(x-1)+\sin(x-1) }{x -1 +\sin(x-1) }\right\}^{1+\sqrt x} = \dfrac{1}{4} \\ \displaystyle\lim_{x\to1}\left\{\dfrac{-a(x-1)+\left(x-1 -\frac{(x-1)^3}{3!} +\frac{(x-1)^7}{7!}+\cdots \right) }{x -1 +\left(x-1 -\frac{(x-1)^3}{3!} +\frac{(x-1)^7}{7!}+\cdots \right) }\right\}^{1+\sqrt x} = \dfrac{1}{4} \\ \displaystyle\lim_{x\to1}\left\{\dfrac{-a +\left(1 -\frac{(x-1)^3}{3!(x-1)} +\frac{(x-1)^7}{7!(x-1)}+ \cdots \right) }{1 +\left(1 -\frac{(x-1)^3}{3!(x-1)} +\frac{(x-1)^7}{7!(x-1)}+\cdots \right) }\right\}^{1+\sqrt x} = \dfrac{1}{4} \\ \displaystyle\lim_{x\to1}\left\{\dfrac{-a +\left(1 -\frac{(x-1)^2}{3!} +\frac{(x-1)^6}{7!}+ \cdots \right) }{1 +\left(1 -\frac{(x-1)^2}{3!} +\frac{(x-1)^6}{7!}+\cdots \right) }\right\}^{1+\sqrt x} = \dfrac{1}{4} \\ \displaystyle\lim_{x\to1}\left\{\dfrac{-a +1 }{1 +1 }\right\}^{1+\sqrt 1} = \dfrac{1}{4} \implies \dfrac{(-a+1)^2}{4}=\dfrac{1}{4} \implies a = 0, 2 The answer that satisfy the limit is 0 0 .


In response to Fish Bacon query . If we input a = 2 a =2 then limit will be undefined since function we have is like f ( x ) g ( x ) f(x)^{g(x)} and as x 1 x\to 1 , g ( x ) g(x) is approching 2 2 and f ( x ) < 0 f(x) <0 which undergoes the complex form. To be limit defined f ( x ) 0 f(x)\geq 0 which is only possible if a = 0 a=0 .

In the final step, a comes out to be 0 and 2. But we discard 2, please provide a justification of that in your answer.

Fish Recon - 3 years ago

Log in to reply

I have added the clarification. :)

Naren Bhandari - 3 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...